TEMPERATURE RESPONSES TO QUASI-100-YR SOLAR VARIABILITY DURING THE PAST 6000 YEARS BASED ON δ18O OF PEAT CELLULOSE IN HONGYUAN, EASTERN QINGHAI-TIBET PLATEAU, CHINA - Xu H.; Hong Y.; Lin Q.; Zhu Y.; Hong B.; Jiang H. (My University, 2006)
During the past 6000 years, the temperature variation trend inferred from δ18O of peat cellulose in a peat core from Hongyuan (eastern Qinghai-Tibet plateau, southwestern China) is similar to the atmospheric 14C concentration trend and the modeled solar output trend. The general trend of Hongyuan δ18O during the past millennium also coincides well with the atmospheric 14C concentration trend, the 10Be concentration trend in an ice core from the South Pole, the reconstructed total solar irradiance trend, as well as the modeled solar output trend. In addition, temperature events also correspond well to solar perturbations during the past 6000 years. Therefore, the driving force of Holocene temperature variations should be properly ascribed to solar activity. The spectrum analysis further illustrates that quasi-100-yr fluctuation of solar activity was probably responsible for temperature variations in northeast Qinghai-Tibet plateau during the past 6000 years. © 2005 Elsevier B.V. All rights reserved.
Keywords: CHINA; OXYGEN ISOTOPIC COMPOSITION; PEAT; QINGHAI-TIBET PLATEAU; SOLAR ACTIVITY; TEMPERATURE; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен